Radiography, CT, and MRI Diagnosis of Enzootic Nasal Tumor in Goats Infected With Enzootic Nasal Tumor Virus - Li, Ling-xu; Lv, Ying-jun; Guo, Qing-yong; Liao, Yun; Guo, Yi-wen; Su, Ze-nan; Yao, Da-wei; Yang, De-ji (Frontiers in Veterinary Science, 2022)
The aim of this study was to describe radiography, computed tomography (CT), and magnetic resonance imaging (MRI) findings of enzootic nasal tumors in goats infected with enzootic nasal tumor viruses. Five of six goats with a mean age of 2 years, showed clinical signs of respiratory disease. Head radiographs showed increased density of the unilateral or bilateral nasal cavity in four goats, and a CT scan showed that the space-occupying lesion of the nasal cavity originated from the ethmoid bone and was enhanced homogeneously postcontrast in all goats. The nasal concha was destroyed and the paranasal sinus mucosa was thickened and filled with fluid in some goats. On MRI, the mass exhibited equal or slightly higher signal intensity on T2 weighted images, equal signal intensity on T1 weighted images, a high signal on fluid-attenuated inversion recovery images and heterogeneous enhancement postcontrast. After dissection, histopathological examination of the mass and virus genome detection of the nasal secretions confirmed that the intranasal mass was a low-grade adenocarcinoma and that the goats were infected with enzootic nasal tumor virus type 2. In conclusion, CT and MRI have high diagnostic values for enzootic nasal tumors because they match the postmortem findings and are more accurate than radiography.